THE EFFECT OF STEM-PjBL AND ADVERSITY QUOTIENT ON HIGH SCHOOL STUDENTS’ PROBLEM SOLVING ABILITY - Eki Sutisna; Aan Hendrayana; Anwar Mutaqin (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2024)
The mathematics learning development is colored by advances in science and technology. The integration of STEM (Science, Technology, Engineering, and Mathematics) in today's mathematics learning should be a priority. This is due to the improving need for Human Resources who are competent in the STEM field, includes the ability to solve complex problems. In digital era, Mathematical Problem Solving Ability (KPMM) is needed. The students' are required to be competent in technology. By collaborating STEM-PjBL in learning activity, it is expected. that students' have KPMM improvement. This research aims to determine the effect of STEM-PjBL and Adversity Quotient (AQ) on KPMM. This research used quantitative approach with quasi-experimental method and nonequivalent pretest-posttest research design. This research used two classes, namely the experimental class for STEM-PjBL model and the control class for scientific approach. This research was conducted in one of the high schools in Tangerang with a population of all students in grade XI with sample around to 39 students who were selected by purposive sampling. This study used two instruments, namely the problem solving ability test instrument and the AQ non-test instrument. The results showed that STEM-PjBL and scientific learning had a positive effect on KPMM. Meanwhile AQ also had a positive effect in all categories. Beside that, this research also showed there was no interaction effect between the two of learning models and AQ on students' KPMM. Students who received STEM-PjBL and scientific learning obtained n-gain of 0.48 and 0.35, which means that there was an improvement in KPMM with a quite good category.Perkembangan pembelajaran matematika diwarnai oleh kemajuan sains dan teknologi. Integrasi STEM (Science, Technology, Engineering, and Mathematics) dalam pembelajaran matematika saat ini harus menjadi prioritas. Hal ini karena meningkatnya kebutuhan Sumber Daya Manusia (SDM) yang berkompeten dalam bidang STEM, mencakup kemampuan pemecahan masalah yang kompleks. Penelitian ini bertujuan untuk mengetahui pengaruh model STEM-PjBL dan Adversity Quotient (AQ) terhadap Kemampuan Pemecahan Masalah Matematis (KPMM). Penelitian ini menggunakan pendekatan kuantitatif dengan metode kuasi eksperimen dan desain penelitian nonequivalent pretest-posttest. Penelitian ini dilaksanakan di salah satu SMA kota Tangerang dengan populasi seluruh siswa kelas XI dengan sampel sebanyak 39 siswa yang dipilih secara purposive sampling. Penelitian ini menggunakan dua kelas, kelas eksperimen untuk model STEM-PjBL dan kelas kontrol untuk pendekatan saintifik. Penelitian ini menggunakan dua instrumen yaitu instrumen tes kemampuan pemecahan masalah dan instrumen non-tes AQ. Hasil penelitian ini menunjukkan bahwa STEM-PjBL dan pembelajaran saintifik memiliki pengaruh positif terhadap KPMM. Begitupun dengan AQ yang juga berpengaruh positif terhadap KPMM di semua kategorinya. Selain itu, penelitian ini juga menunjukkan tidak adanya pengaruh interaksi antara kedua model pembelajaran dan AQ terhadap KPMM. Siswa yang mendapatkan model STEM-PjBL dan pembelajaran Saintifik memperoleh n-gain sebesar 0,48 dan 0,35 yang artinya terjadi peningkatan KPMM dengan kategori cukup baik.